2020
DOI: 10.1371/journal.pone.0243306
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the double loop knot stitch and Kessler stitch for Achilles tendon repair: A biomechanical cadaver study

Abstract: Tendon elongation after Achilles tendon (AT) repair is associated with the clinical outcome. Reliable suture techniques are essential to reduce gap formations and to allow early mobilization. Cyclic loading conditions represent the repetitive loading in rehabilitation. The aim of this study was to compare the Kessler stitch and double loop knot stitch (DLKS) in a cyclic loading program focussing on gap formation. Sixteen human cadaveric ATs were transected and sutured using either the Kessler stitch or DLKS (e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…The search strategy yielded 2949 entries. Sixteen studies met the inclusion criteria for quantitative synthesis [5, 6, 10, 12, 14, 18, 20, 23, 24, 28, 30, 46, 50, 54, 75, 77]. The study search and selection flowchart, with reasons for exclusion, is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The search strategy yielded 2949 entries. Sixteen studies met the inclusion criteria for quantitative synthesis [5, 6, 10, 12, 14, 18, 20, 23, 24, 28, 30, 46, 50, 54, 75, 77]. The study search and selection flowchart, with reasons for exclusion, is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…All studies described the method used to simulate an ATR, with transection using a conventional scalpel being used across all studies. This transverse cut was performed at a distance from the calcaneal insertion of 2 [24], 3 [54], 4 [5, 12, 14, 23, 30, 46, 75, 77], 4.5 [18, 28], 5 [6, 20, 50] and 6 cm [10].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The proximal end of Achilles tendon is sutured with three transverse crosses of sutures by using an eccentric sleeve. We simplified the complex steps of Achillon and PARS repair and decreased the number of knots, facilitating the gliding of the Achilles tendon with the surrounding tissue after long-term repair and reducing the formation of keloids [ 42 , 43 ]. So, this Mini-open repair system can reduce the risk of suture reactivity and make the broken end smoother.…”
Section: Discussionmentioning
confidence: 99%
“…Differences in treatment specifics within groups may have further limited the validity of pooling studies to perform this analysis. Recent evidence has found that distinct surgical variations and variations in postoperative protocols result in different degrees of tendon elongation [8,18,27,30,40,72,86]. Further, post-treatment tendon elongation has been associated with lower patient-reported outcomes scores and reduced plantarflexion strength [28,79,91] Similarly, return to work and sport analyses were not performed because of very low evidence quality and poor assessment of the endpoints in question.…”
Section: Limitationsmentioning
confidence: 99%